(untitled) (Bangladesh Journal of Pathology, 2010)
Keywords: Glycosylated hemoglobin; low-density lipoprotein cholesterol, type 2 diabetes DOI: 10.3329/bjpath.v25i1.4125 Bangladesh J Pathol 25(1): 10-13